2015
DOI: 10.5114/pdia.2015.48063
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and character profiles of patients with chronic idiopathic urticaria

Abstract: IntroductionPsychosocial factors have been implicated as being important in the onset and/or exacerbation of urticaria.AimTo examine both personality factors of patients with chronic idiopathic urticaria (CIU) and the correlations between illness duration, severity of itching, urticaria activity score (UAS) and temperament-character dimensions.Material and methodsA total number of 70 CIU patients and 60 healthy individuals were included in the study. The Temperament and Character Inventory (TCI) was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…The pruritus severity is significantly associated with impaired sleep quality in patients with CSU ( 5 15 16 ). We also found that the pruritus severity has been correlated with PSQI, VAS and RLS scores in patients with CSU ( 17 18 ). We believe that the reason for this increase of RLS score in patients with CSU is pruritus.…”
Section: Discussionsupporting
confidence: 56%
“…The pruritus severity is significantly associated with impaired sleep quality in patients with CSU ( 5 15 16 ). We also found that the pruritus severity has been correlated with PSQI, VAS and RLS scores in patients with CSU ( 17 18 ). We believe that the reason for this increase of RLS score in patients with CSU is pruritus.…”
Section: Discussionsupporting
confidence: 56%
“…Disease lasts more than 6 weeks and is characterized by recurrent wheals accompanied by pruritus [1, 2]. The CU is perceived as a psychodermatological condition, so psychological factors can influence hives development and exacerbation [3–6]. Additionally, the disease itself and its consequences can affect psychological well-being and worsen quality of life [79].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report that chronic urticaria patients have a sensitive personality, are depressive, can be more hysterical, and have suspicious personality traits compared to healthy controls. 10,11 Irrespective of that, it is essential to screen CU patients for these conditions so as to treat them appropriately, which should help in the management of the chronic urticaria for better outcomes.…”
mentioning
confidence: 99%